Propuesta de un modelo de integración de sistemas de gestión de calidad para simplificar los procesos basados en las Normas ISO9001, ISO14001 & OHSAS 18001 en la industria manufacturera - Villanueva Molina, Daniel (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
In front to the current necessity of companies regarding to ensure the product and services quality requirements specified by those key customers demanding as a first requirement to do businesses, the fulfilment of management systems focused into continuous improvement, furthermore the commitment to safeguard the safety of their employees and protect the environment integrity; there have arisen organisms supported by a regulatory qualified entity, which validate that the companies are fulfilling everything previous by means of the certification of their systems and processes; This is why the world class companies and those in search of the excellence, have met forced to comply with these minimal requirements to be able to compete in an international field. Nowadays, the most demanded standards are from the ISO9000, ISO14000 and OHSAS18000 families, for which contract the services of certification of organisms accredited for each of them of an individual way, which needs a great investment of time, money and effort on the part of the organizations and employees. Based on this premise, the aim of this project is to integrate the most common existing systems of management in the current organizations (Quality, Environment, Safety and Occupational Health) in one system, which in an integral way allows to simplify the systemic approach of the processes of the organizations and to reverberate in bringing down costs of certification, time invested to the improvement of processes, audits, quantity of internal auditors needed to evaluate the performance of the different certifiable systems; and as well as get robust systems of management making them more reliable and flexible. This will be also reflected in the positive perception that the internal and external clients have on the company.

Ante la necesidad actual de las empresas de asegurar tanto el cumplimiento de los requisitos de calidad de los productos y servicios especificados por aquellos clientes clave que exigen como primer requisito para hacer negocio, tener sistemas de gestión enfocados hacia la mejora continua, así como el compromiso de salvaguardar la seguridad de sus empleados y proteger la integridad del medio ambiente; han surgido organismos avalados por un ente regulador calificado, que validan que las compañías estén cumpliendo todo lo anterior mediante la certificación de sus sistemas y procesos; por lo que las empresas de clase mundial y aquellas en busca de la excelencia, se han visto forzadas a cumplir con estos requerimientos mínimos para poder competir en un ámbito internacional. En la actualidad las normas más demandadas son de la familia de normas ISO9000, ISO14000 y OHSAS 18000, para las cuales se contratan los servicios de certificación de organismos acreditados para cada una de ellas de manera individual, lo cual requiere una gran inversión de tiempo, dinero y esfuerzo por parte de las organizaciones y empleados. Basado en esta premisa, el objetivo de este proyecto es integrar los sistemas de gestión más comunes existentes en las organizaciones actuales (Calidad, Medio Ambiente, Seguridad y Salud Ocupacional) en un solo sistema, que de manera integral permita simplificar el enfoque sistémico de los procesos de las organizaciones y repercuta en abatir costos de certificación, tiempo invertido a la mejora de procesos, auditorias, cantidad de auditores internos requeridos para evaluar el desempeño de los diferentes sistemas certificables; y así como robustecer los sistemas de gestión haciéndolos más confiables y flexibles.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2012-0209; Necesidad; Empresas; Manufactura; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5998